Study on Deformation characteristics and damage evolution of water-bearing coal under cyclic loading - Tianyu Xin; Yang Ji; Junguang Wang; Gang Bai; Veiji Sun; Jinyu Li; Bing Liang (Results in Engineering)
To study cyclic loading effects on hydrated coal deformation, triaxial tests with variable loading paths were performed using acoustic emission(AE) monitoring. Results show that cumulative and irreversible coal strains increase cyclically with diminishing increments. Experimentally, raising cyclic stress lower limit, load amplitude, and moisture content reduced stress peaks by 3.668, 3.808, and 9.159 MPa respectively. Under the experimental conditions, the hierarchy of factors affecting coal's mechanical performance is determined as: moisture content variation > regulatory effect of cyclic stress lower limit > influence of cyclic stress amplitude. The cumulative AE counts exhibited gradual growth, fluctuating growth, and steep escalation trends respectively. During cyclic loading phases, coal specimens subjected to higher cyclic stress lower limits and larger load amplitudes displayed elevated cumulative AE counts, closely linked to the propagation of internal fractures. However, when cumulative AE counts reached their peaks, specimens with smaller cyclic amplitudes and lower cyclic stress limits exhibited higher AE accumulations. This is attributed to the inhibitory effect of high-stress cyclic conditions on the long-term accumulation of AE events. Dry coal specimens consistently showed higher cumulative AE counts during both cyclic loading and peak phases compared to hydrated coal, confirming water’s inhibitory role in AE signal accumulation. The temporal dependency of coal damage evolution during testing was evident, leading to the development of a time-dependent AE damage evolution model for hydrated coal. These findings provide theoretical guidance for deep coal mining practices.